I pledge allegiance : a believer's guide to kingdom citizenship in twenty-first-century America - Crump, David, 1956- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2018)
Bitter partisan conflict. State-sanctioned torture. Economic injustice. Ethical corruption. Even a cursory glance over daily news headlines shows a stark contrast between the American political state and the kingdom of heaven. Where, then, does the Christian's ultimate allegiance lie? In I Pledge Allegiance David Crump issues a clarion call to Jesus's twenty-first-century disciples, stirring them up to heed God's word and live out their kingdom citizenship here on earth. Closely examining the ethical teachings of Jesus and his apostles in the New Testament and using real-world examples to illustrate the vital issues at stake, Crump challenges Christians to embrace the radical, counterintuitive, upside-down way of Jesus--a way of living and thinking that turns the world's values on their head, smashes through stale political and cultural conventions, and welcomes God's kingdom into the very heart of our shared society. - From publisher.
Whom would Jesus torture? -- What is the kingdom of God? -- Seek first the kingdom of God -- Living with dual citizenship -- Aliens in a world of politics -- How is the kingdom political? -- When disobedience is a virtue -- Taking exception to exceptionalism -- Does kingdom service permit military service? -- God hates poverty -- Blessed are those who suffer because of me -- Being a kingdom church.
Includes bibliographical references and indexes.
Keywords: Christianity -- United States; Christian life -- United States; Christianity -- 21st century; RELIGION / Christian Life / Social Issues; RELIGION / Christian Theology / General